Spontaneously released Neisseria meningitidis outer membrane vesicles as vaccine platform: production and purification. Issue 47 (8th November 2019) - Gerritzen, Matthias J.H.; Salverda, Merijn L.M.; Martens, Dirk E.; Wijffels, René H.; Stork, Michiel
Highlights: Spontaneous outer membrane vesicles (OMVs) differ in protein composition from extracted OMV. Spontaneously released N. meningitidis OMVs can be produced with high yield by high oxygen levels. Optimized tangential flow microfiltration recovers 90% of OMVs from the bacterial culture. N. meningitidis OMVs expressing heterologous antigens can be produced. Abstract: Outer membrane vesicles (OMVs) are nanoparticles produced by Gram-negative bacteria that can be used as vaccines. The application of OMVs as vaccine component can be expanded by expressing heterologous antigens on OMVs, creating an OMV-based antigen presenting platform. This study aims to develop a production process for such OMV-based vaccines and studies a production method based on meningococcal OMVs that express heterologous antigens on their surface. As a proof of concept, the Borrelia burgdorferi antigens OspA and OspC were expressed on Neisseria meningitidis OMVs to create a concept anti-Lyme disease vaccine. Production of OMVs released in the culture supernatant was induced by high dissolved oxygen concentrations and purification was based on scalable unit operations. A crude recovery of 90 mg OMV protein could be obtained per liter culture. Expressing heterologous antigens on the OMVs did result in minor reduction of bacterial growth, while OMV production remained constant. The antigen expression did not alter the OMV characteristics. This study shows that production of well characterized OMVs containing heterologous antigens is possible with high yields by combining high oxygen concentrations with an optimized purification process. It is concluded that heterologous OMVs show potential as a vaccine platform.